Influence of the Electrolyte Salt Concentration on the Rate Capability of Ultra‐Thick NCM 622 Electrodes. Issue 11 (4th August 2020) - Kremer, Lea Sophie; Danner, Timo; Hein, Simon; Hoffmann, Alice; Prifling, Benedikt; Schmidt, Volker; Latz, Arnulf; Wohlfahrt‐Mehrens, Margret
Abstract: In traditional Li‐ion batteries, the electrolyte consists of a Li‐conducting salt dissolved in organic solvents at a concentration of ∼ 1 mol L −1 (1 M). In this work, we use increased LiPF6 concentrations between 1 and 2.3 M to investigate the influence of the electrolyte salt concentration on the rate capability of ultra‐thick (49.5 mg cm −2 ) and thin (5.6 mg cm −2 ) NCM 622 electrodes, respectively. At higher electrolyte salt concentrations than 1 M, thin electrodes suffer from increased polarization, due to a higher viscosity and a reduced ionic conductivity. In contrast, by raising the salt concentration from 1 to 1.9 M the discharge capacity of ultra‐thick electrodes is increased by more than 50 % for current densities above 3 mA cm −2, which significantly improves their rate capability. 3D microstructure resolved simulations revealed that this effect results from the mitigation of Li‐ion depletion in the electrolyte filled pore space of ultra‐thick electrodes. Abstract : Thick as thieves : Ultra‐thick electrodes offer a larger areal capacity and higher active to passive material ratio than state of the art Li‐ion battery electrodes. However, they suffer from low rate capabilities, due to mass transport limitations in the electrolyte. Concentrated electrolytes above 1 mol L −1 increase the density of charge carriers, which mitigates Li‐ion depletion and improves the energy density of ultra‐thick electrodes at high current densities.